Investigating trajectories of social recovery in individuals with first-episode psychosis: A latent class growth analysis. (December 2015) - Hodgekins, Jo; Birchwood, Max; Christopher, Rose; Marshall, Max; Coker, Sian; Everard, Linda; Lester, Helen; Jones, Peter; Amos, Tim; Singh, Swaran; Sharma, Vimal; Freemantle, Nick; et al.
Abstract : Background: Social disability is a hallmark of severe mental illness yet individual differences and factors predicting outcome are largely unknown. Aim: To explore trajectories and predictors of social recovery following a first episode of psychosis (FEP). Method: A sample of 764 individuals with FEP were assessed on entry into early intervention in psychosis (EIP) services and followed up over 12 months. Social recovery profiles were examined using latent class growth analysis. Results: Three types of social recovery profile were identified: Low Stable (66%), Moderate-Increasing (27%), and High-Decreasing (7%). Poor social recovery was predicted by male gender, ethnic minority status, younger age at onset of psychosis, increased negative symptoms, and poor premorbid adjustment. Conclusions: Social disability is prevalent in FEP, although distinct recovery profiles are evident. Where social disability is present on entry into EIP services it can remain stable, highlighting a need for targeted intervention.